PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IV SDN SUMPUT - Anggi Agnes Wibowo; Selvi Cahya Islami; Muhammad Iqbal Amaluddin (Jurnal Muassis Pendidikan Dasar, 2022)
Behind this research is the low learning outcomes of students on the material area and perimeter of squares and rectangles in mathematics. The percentage of students' completeness is only 13%. This happened because of the lack of enthusiasm of students in participating in learning in class and there were still many students who did not listen when the teacher explained the material. In addition, learning also uses more lecture methods which result in students being passive in learning. In response to this, it is necessary to apply an index card match strategy to improve mathematics learning outcomes for the area and perimeter of square and rectangular shapes for fourth grade students at SDN Sumput Sidoarjo. The subjects of this study were fourth grade students of SDN Sumput which consisted of 23 students. The results of the study concluded that: Learning by applying the Index Card Match strategy can improve student learning outcomes. This is evidenced by an increase in student learning outcomes in learning activities in each cycle. In the first cycle, the percentage of success criteria was 13.1%. While in the second cycle the percentage of student success increased to 82.7%. This proves that the index card match (ICM) learning model can improve the learning outcomes of fourth grade elementary school students in the area and perimeter of flat shapes